The prevalence and predictors of food insecurity among HIV-infected women in Cape Town, South Africa: A cross sectional study - Mzimkulu, Olona (Department of Public Health and Family Medicine, 2020)
Background: Food insecurity is a major public health concern in most settings where the Human Immunodeficiency Virus (HIV) is prevalent, and it affects women disproportionately. However, the prevalence of food insecurity and associated risk factors for women who are living with HIV (WLH) in South Africa is under researched. Methods: The researcher conducted a secondary, cross-sectional analysis of 346 HIV-infected women aged between 18 and 45, in Gugulethu, Cape Town. All participants were 12 months postpartum and enrolled into the MCH-ART study, a large implementation science study of antiretroviral use in pregnancy. For this study, women completed a 10-item household food security questionnaire that categorised food security status into household-level food insecurity, individual level food insecurity and children hunger. Using this tool, the level of food insecurity was categorised as food insecurity (“yes” to up to four questions), experiencing food insecurity (“yes” to five questions or more) and free from food insecurity (“no” to all questions). Results: Overall, the mean age was 29 years (SD: 5.46); 25 % of the women completed high school; 61 % were unemployed; nearly 66 % were free from food insecurity; and 25 % experienced food insecurity. Women who were employed were less likely to experience food insecurity when compared to those who were not employed (OR=0.54; 95 % CI: 0.32-0.90; p= 0.01). Those who completed high school were associated with food security than the ones who did not complete high school (OR= 0.5; 95 % CI: 0.28-0.97; p= 0.04). After adjusting for maternal age, marital and cohabiting status, education attainment, and parity, employment remained a significant predictor of experiencing food security (AOR= 0.55; 95 % CI: 0.32- 0.95 p=0.03) and educational attainment was no longer associated with food insecurity. Conclusions: The prevalence of food insecurity was relatively low in the urban-based sample of HIV-infected women. However, most of these HIV-infected women were obese and overweight. Thus, there is a clear need for more research to explore issues of food insecurity and nutrition in HIV-infected South African women.